2007
DOI: 10.1007/s00213-007-0884-y
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and the pupil: why diazepam-induced sedation is not accompanied by miosis

Abstract: Diazepam-induced sedation is not accompanied by any change in either the sympathetic or parasympathetic influence on the iris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 89 publications
(140 reference statements)
1
42
0
Order By: Relevance
“…Psychophysiology offers a more objective outcome measure. However, diazepam does not lead to any change in papillary diameter (Hou et al 2007, Fig. 1).…”
Section: Principles Of Psychophysiological Methods As Applied In Psycmentioning
confidence: 95%
See 3 more Smart Citations
“…Psychophysiology offers a more objective outcome measure. However, diazepam does not lead to any change in papillary diameter (Hou et al 2007, Fig. 1).…”
Section: Principles Of Psychophysiological Methods As Applied In Psycmentioning
confidence: 95%
“…The CFFF is a test that has been in usage since the 1950s, and it is well accepted as a psychophysiological measure of arousal (Tomkiewicz and Cohen 1970). Hou et al (2007) showed a significant effect of diazepam on the CFFF (Fig. 1), suggesting that diazepam does indeed have an effect on arousal, and this can be measured both subjectively and objectively.…”
Section: Principles Of Psychophysiological Methods As Applied In Psycmentioning
confidence: 95%
See 2 more Smart Citations
“…The effects of some drugs, therefore, might somehow confound the relationship between the outcome measures of the study. As for the pupillary effects of the drugs, changes both in pupillary measurements and central alertness levels have been simultaneously investigated for antidepressants [34], central a2-adrenoceptor agonists and antagonists [22], anti-Parkinsonian drugs [35], benzodiazepan [36], modafinil [37], and anti-hypertensive drugs [38]. In these studies, the direction and amplitude of changes in pupillary measurements or central alertness varied depending on the effect of each drug.…”
Section: Limitationsmentioning
confidence: 99%